Analysis Of Drums Stick Spent Layer Hens With The Addition Of Cmc (Carboxymethyl Cellulose) As A Thickening Ingredient - Meliyanti, Nur Anggi; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
Spent layer hens are that no longer productive for laying eggs, Some processed restructure meats are from the drums stick layer hens. So it is necessary to add food ingredients that can improve the texture of drums stick, namely Carboxymethyl Cellulose (CMC). T products of spent layer hens by analyzing the effect of adding CMC as much as 0.5%, 1% and 1.5% on the quality of chicken dragon legs from organoleptic. This research was conducted in October – November 2022 at the Tata Boga workshop, Department of Family Welfare Sciences, Faculty of Hospitality Tourism, Universitas Negeri Padang. This type of research is a pure experiment using the complete randomized design method (RAL) consisting of 4 treatments and 3 repetitions, to analyze the quality of the drums stick through organoleptic tests involving 3 expert panelists. The data obtained are then tabulated and continued with statistical analysis (ANAVA), if Fhitung ≥ Ftabel it will be continued with the Duncan test. The results showed that CMC enhancers affect shape, texture and taste while in other indicators they have no effect in terms of color and aroma. The best research results of Carboxymethyl Cellulose (CMC) were found in the X1 treatment. The highest achievement score overall was neat shape 3.78 (0.5%), uniform shape 3.89 (0.5%), golden yellow color 3.67 (0.5%), aroma 3.89 (0.5%), chewy texture 3.78 (0.5%), and savory taste 4.00 (0.5%). The addition of CMC has a significant influence between 0.5%,1% and 1.5% on the quality of drums stick, namely the quality of chewy texture and the distinctive taste of dragon legs. The results of the quality test of drums stick with the addition of the best CMC, namely in the X₁ treatment with the addition of CMC as much as 0.5.